2020
DOI: 10.3389/fmicb.2020.00584
|View full text |Cite
|
Sign up to set email alerts
|

Deadly Puppy Infection Caused by an MDR Escherichia coli O39 blaCTX–M–15, blaCMY–2, blaDHA–1, and aac(6)-Ib-cr – Positive in a Breeding Kennel in Central Italy

Abstract: Antimicrobial consumption in veterinary medicine has led to the spread of multi drug-resistance in clinically important bacteria, with the companion animals and their environment involved as emerging reservoirs. While CTX-M-15 and CMY-2 acquired β-lactamases have been widely detected in the bacterial population of companion and breeding animals in European area, DHA-1 enzymes have been rarely reported in veterinary medicine. The aim of the study was to characterize the Escherichia coli associated with mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Finally, we demonstrate that similar plasmid sequences were present in strains from different sample groups, thus likely indicating mobile genetic element transmission, and underlining the importance of plasmid-driven spread of antimicrobial resistance independent of the host's phylogenetic background (Schaufler et al, 2016a;Ranjan et al, 2018). Interesting in addition to similarities among strains from the Rwandan setting is in particular the close relationship to an external plasmid, which has been obtained only recently (Marchetti et al, 2020). This highlights the sometimes global spread of such mobile genetic elements and their bacterial hosts.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Finally, we demonstrate that similar plasmid sequences were present in strains from different sample groups, thus likely indicating mobile genetic element transmission, and underlining the importance of plasmid-driven spread of antimicrobial resistance independent of the host's phylogenetic background (Schaufler et al, 2016a;Ranjan et al, 2018). Interesting in addition to similarities among strains from the Rwandan setting is in particular the close relationship to an external plasmid, which has been obtained only recently (Marchetti et al, 2020). This highlights the sometimes global spread of such mobile genetic elements and their bacterial hosts.…”
Section: Discussionmentioning
confidence: 52%
“…We also compared some of our plasmid sequences of representative strains (criteria: top BLAST-hits) against a publicly available reference plasmid pIV_IncHI2_CTX_M_15 (Marchetti et al, 2020; Supplementary Figure 3). This bla CTX−M−15containing plasmid has been originally obtained from an E. coli ST58 strain causing a deadly puppy infection in Italy in 2019.…”
Section: Mobile Genetic Elementsmentioning
confidence: 99%
“…This IncHI2 plasmid has been isolated from a variety of Enterobacteriaceae species including the Enterobacter cloacae complex, Salmonella enterica , Klebsiella pneumoniae , Citrobacter freundii and E. coli [78–81]. It has been suggested that the reason for the successful spread of this IncHI2 plasmid is because it harbours numerous metal resistance genes [80].…”
Section: Resultsmentioning
confidence: 99%
“…AAC(6′)-Ib-cr has two amino acid changes, Trp102Arg and Asp179Tyr, which together are necessary for the enzyme’s ability to acetylate the antibiotic [ 103 ]. The presence of a gene encoding AAC(6′)-Ib-cr was confirmed in clinical enrofloxacin-resistant strains of E. coli [ 104 ] and S. Indiana [ 105 ].…”
Section: Mechanisms Of Resistance To Enrofloxacinmentioning
confidence: 99%